2020
DOI: 10.1111/jocd.13908
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum level of interleukin‐15 in vitiligo patients and its correlation with disease severity but not activity

Abstract: Background Vitiligo is a common acquired disorder of depigmentation. Its pathogenesis entails a T helper (Th) 1‐cytotoxic T (cT) lymphocytes mediated autoimmune melanocyte destruction. Interleukin (IL)‐15 is one of the IL‐2 family of cytokines and shares several actions with IL‐2. IL‐15 enhances survival, maturation, and functional activity of natural killer, neutrophils, and dendritic cells. Furthermore, it potentiates survival, maturation, and cytotoxicity of memory cT cells. IL‐15 has been shown to play a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Results of that study revealed that serum IL-15 level, in patients with vitiligo, was significantly higher in comparison with the control group (P=0.001). Also, a significant positive correlation was found between serum IL-15 level and VES score (P=0.001), whereas there was no significant correlation between IL-15 level and VIDA score as well as the disease duration (19) .…”
Section: Discussionmentioning
confidence: 84%
“…Results of that study revealed that serum IL-15 level, in patients with vitiligo, was significantly higher in comparison with the control group (P=0.001). Also, a significant positive correlation was found between serum IL-15 level and VES score (P=0.001), whereas there was no significant correlation between IL-15 level and VIDA score as well as the disease duration (19) .…”
Section: Discussionmentioning
confidence: 84%
“…It has been established that IL-15 seems to participate in IL-17 regulation and maintenance of TRM signals (80), with the latter responsible for long-term maintenance and potential relapse of vitiligo (81). The study has demonstrated a higher serum level of IL-15 in vitiligo patients than in controls, highly associated with epidermal H 2 O 2 content and the disease activity (82,83).…”
Section: Il-15 and The Inhibitorsmentioning
confidence: 97%
“…IL-15 expression in the epidermis and serum of patients with vitiligo was significantly higher when compared with healthy controls, and highly correlated with H 2 O 2 levels [ 68 ]. Oxidative stress promoted IL-15 and IL-15Rα expression, and also IL-15 trans-presentation by activating NF-κB signaling in keratinocytes, thereby contributing to effector memory T cell (CD 8 + T EM ) activation by IL-15-JAK-STAT signaling pathway [ 69 ].…”
Section: Oxidative Stress Stimulates Damp Release and Worsens Vitiligomentioning
confidence: 99%